The Effect of Hypoxia on the Soluble Molecules of Human Umbilical Cord-Derived Mesenchymal Stem Cells (UC-MSCs) - Widyatmoko, Agus; Alif, Iffan; Irawan, Risky Candra Satria; Handoyo, Frigi Eko; Sidiq, Husni Ahmad (Stem Cell and Cancer Research (SCCR), 2022)
Background: Umbilical cord-derived stem cells (UC-MSCs) are essential cell sources for cell-based therapies in regenerative medicine. Hypoxia is a key element of the stem cell niche and crucial for the preservation of UC-MSCs properties. The normal growth conditions for UC-MSCs are under atmospheric oxygen concentrations of 20–21%. However, the administration of UC-MSCs in inflammatory conditions provides oxygen-deficient environments. Thus, treating UC-MSCs with low oxygen exposure provides them with more survival and recovery potential. Objective: In this study, we assessed the impact of hypoxia incubation for 12 h on the UC-MSCs proteome. Methods: UC-MSCs were isolated from UC patients regarding informed consent. At passage 5, in 80% confluent, UC-MSCs were incubated in 5% O2 for 12 h. The morphology of UC-MSCs was assessed using a microscope. The level of FGF-2, FGF-8, TNF-α, and HSP-70 were analyzed using ELISA. Results: Hypoxic condition could change their morphology and enhance the cellular density compared to normoxic conditions in vitro. The level of FGF-2, FGF-8, TNF-α, and HSP-70 were significantly increased after the hypoxic condition of UC-MSCs compared to normoxia. Conclusion: Our findings suggest that the hypoxic condition was able to induce survival capacity and soluble molecules secreted by UC-MSCs.